Effects of natural carotenoid (carrot and red bell pepper) on growth performance, digestive enzymes and antioxidant enzymes in koi, Cyprinus rubrofuscus - Abbas Zamani (تغذیه آبزیان)
Introduction: One of the most important indices in increasing the marketability of ornamental fish is the favorite growth. The main pigment in many fish species is carotenoid, employing to improve their antioxidant capacity and immune system. Nowadays, in many studies, using carotenoid obtained from agricultural sources, especially carotenoids found in plants, has been considered in fish diet and shown a high capacity than the artificial carotenoid in order to improve fish growth. The aim of this study was to use carrot, Daucus carota and red bell pepper, Capsicum frutscene grossum powders as rich sources of carotenoids in the diet of koi, Cyprinus rubrofuscus fry and to investigate their effects on growth performance, digestive and antioxidant enzymes. Materials and methods: Four experimental dietary treatments including the control  (without plant powder; D1), 2% carrot powder (D2), 2% red bell pepper powder (D3), and also 2% containing a mixture of carrot powder (1%) and red bell pepper (1%; D4) were prepared as isonitrogenous and isocaloric diets in triplicate. The effect of prepared diets was evaluated on growth performance, digestive enzymes (trypsin and amylase) and antioxidant activity including superoxide dismutase (SOD) and catalase in koi (weight: 1.10 ± 0.20 g) for 8 weeks. Results and discussion: The results obtained from body weight gain, specific growth rate and condition factor showed that there was no significant difference among the experimental diets, although they were higher in D2, D3 and D4 compared to D1. The lowest food conversion ratio was observed in D2, however, no significant difference was recorded among the treatments. Also, survival rate in experimental diets was 100%. Protein and lipid efficiency ratios as well as the activity of trypsin and amylase were lower in D1 than in   D2, D3 and D4, albeit without any significant difference. According to the results, antioxidant enzyme activities including SOD and catalase significantly decreased in D2 compared to D1 (control) in both before and after stress (p<0.05). Conclusion: Based on the results, at the aforementioned levels of carrot powder and red bell pepper did not exhibit any negative effects on the growth performance, digestive enzymes and antioxidant activity of koi. Funding: The author has no sources of funding for the present work. Conflicts of interest: Authors have no conflict of interest to declare for the publication of the present work. Acknowledgments: The author would like to thank the helpful assistance offered by the laboratory staff in Fisheries Department of Malayer University.